Integrative Leadership of School Administrators Affecting to 21st Century Learning Skills of School Under Secondary Educational Service Area Office Loei Nong Bua Lam Phu: Integrative Leadership of School Administrators Affecting to 21st Century Learning Skills of School Under Secondary Educational Service Area Office Loei Nong Bua Lam Phu - Poonsawat, Adisorn; Sonchan, Chissanapong (RATANABUTH JOURNAL, 2023)
The purposes of this research were to 1) study the level of integrative leadership of school administrators, 2) study the level of 21st century learning skills of school, 3) study the relationship between the integrative leadership of school administrators and the 21st century learning skills of school, 4) study the integrative leadership of school administrators affecting to 21st century learning skills of school and 5) create forecasting equation of the integrative leadership of school administrators affecting to 21st century learning skills of school under Secondary Educational Service Area Office Loei Nongbualamphu. The sample consisted of 323 administrators and teachers in the school under Secondary Educational Service Area Office Loei Nongbualamphu. Using stratified random sampling. The instrument used in the research was a rating scale of 5 levels questionnaire with the reliability at 0.976. The statistics used for data analysis were frequency, percentage, mean, standard deviation, Pearson’s product moment correlation coefficient, and stepwise multiple regression analysis. The results of the research showed that: 1) The integrative leadership of school administrators under Secondary Educational Service Area Office Loei Nongbualamphu was at the high level. 2) The 21st century learning skills of school under Secondary Educational Service Area Office Loei Nongbualamphu was at the high level. 3) The integrative leadership of school administrators and the 21st century learning skills of school under Secondary Educational Service Area Office Loei Nongbualamphu had a positive relationship at the .01 level of significance overall. 4) The integrative leadership of school administrators affecting to the 21st century learning skills of school under Secondary Educational Service Area Office Loei Nongbualamphu found that two aspects which were able to predict the 21st century learning skills of school at a statistical significance of the .01 level, Consisted of team work and creativity . The two aspects can predict variable 67.00 percent with a standard error of estimate of ± .27713. 5) The regression equation of raw scores could be summarized and standardized scores could be written as follows: Y´ = 1.628 +.469 (X1) +.180 (X3) Z´Y = .603 (Z1) + .260 (Z3)